Improving Customers’ Satisfaction Strategies in the Banking Industry in Bangladesh - Md Matiur Rahman; Samia Tahsin (CenRaPS Journal of Social Sciences, 2021)
In the high-pitched competitiveness prevailing in the Bangladeshi banking industry, customer satisfaction plays a significant role constituting the main concern based on which consumers select and remain loyal with the company. Thus, this research work provides a model that can augment the elements of customer satisfaction strategies from the aspects that have been gathered from the market and from the available literature. They engage elements such as service quality, Customer Experience (CE) and financial inclusion analyzing the relationship between customer satisfaction, service and CE reflecting a path that indicates that better service and positive CE lead to satisfaction. It is argued that branch availability, along with financial literacy programs, can help reduce the strength of this relationship by enhancing the degree of financial inclusion. In the study, the SERVQUAL model is employed to define variables that influence satisfactions including tangible, reliability, responsiveness, assurance and empathy of which responsiveness and assurance are deemed influential determinants. The recommendations include given these insights, it is suggested that Bangladeshi banks need to formulate and implement particularly targeted solutions to enhancing their performance in the sphere of Customer Satisfaction.